2019
DOI: 10.3390/molecules24122247
|View full text |Cite
|
Sign up to set email alerts
|

Solid State and Solution Study on the Formation of Inorganic Anion Complexes with a Series of Tetrazine-Based Ligands

Abstract: Four molecules (L1–L4) constituted by an s-tetrazine ring appended with two identical aliphatic chains of increasing length bearing terminal morpholine groups were studied as anion receptors in water. The basicity properties of these molecules were also investigated. Speciation of the anion complexes formed in solution and determination of their stability constants were performed by means of potentiometric (pH-metric) titrations, while further information was obtained by NMR and isothermal titration calorimetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Among our recent contributions, we demonstrated the use of tetrazine-based ligands for the coordination of inorganic [15,16] and organic anions [17], emphasizing coordination of halide [18] and pseudohalide anions [19]. Stabilization of anion coordination networks [20], including polyiodide-dense ones [21], has been achieved with s-tetrazine-based ligands through anion-π interactions [22], building on previous evidences of the usefulness of anion-π forces for polyiodide stabilization in perfluoroarene-based systems [23].…”
Section: Introductionmentioning
confidence: 87%
“…Among our recent contributions, we demonstrated the use of tetrazine-based ligands for the coordination of inorganic [15,16] and organic anions [17], emphasizing coordination of halide [18] and pseudohalide anions [19]. Stabilization of anion coordination networks [20], including polyiodide-dense ones [21], has been achieved with s-tetrazine-based ligands through anion-π interactions [22], building on previous evidences of the usefulness of anion-π forces for polyiodide stabilization in perfluoroarene-based systems [23].…”
Section: Introductionmentioning
confidence: 87%
“…35,76 In solution, the joining of anion and ring surfaces requires their desolvation: entropic effects connected with the release of coordinated solvent molecules back into the bulk oftentimes act as a driving force for association in solution. 33,77,81,82 In a sense, recognition of the relevance of ESP, and of in silico calculations in order to understand it, somewhat connects anion-π forces with σ-hole interactions (and thus to the whole discussion) in terms of the underlying basic concepts and required tools. Yet again, we see the "classic" controversial "anion-π" and "lone pair-π" vocabulary shifting towards the new wave "π-hole" interactions, calling for their synthesis and official collocation in a comprehensive view of supramolecular forces.…”
Section: Definitionmentioning
confidence: 99%
“…Englert, Espinosa et al 139 for a further report of layered cation-polyiodide assembly and I⋯I bond investigation). This peculiar organization was made possible by the s-tetrazine-based ligand L2, exploiting the strong anion-π interactions of this family of ligands 35,81,82,140 to stabilize polyiodide sheets.…”
Section: Dalton Transactions Perspectivementioning
confidence: 99%
“…It is known that azines may act as π-acid ligands, which can bind anions above their centres according to their positive electrostatic potentials (ESPs) and their molecular quadrupole moments ( Figure 2) [35]. For example, we have recently shown that s-tetrazine-based ligands can form anion complexes [36] with both inorganic [37][38][39][40][41][42] and organic [43] anions featuring clear anion-π interactions. Spontaneous oxidation of iodide in solution and stabilisation of triiodide (I 3 − ) anions in the solid state were observed in the presence of these s-tetrazine based ligands [38], while bromide was found to interact with the rings of these π-acids, but no oxidation to Br 3 − was detected [39].…”
Section: Introductionmentioning
confidence: 99%